Targeting the Relaxin Pathway for Liver Disease Treatment - Bennett, Robert G. (Eur Med J Hepatol, 2018)
Hepatic fibrosis is a progressive disease with few treatment options outside of transplantation. Relaxin is a member of the insulin/relaxin superfamily of peptide hormones. Originally known for its roles in pregnancy, relaxin promotes reproductive tissue remodelling and regulates vascular changes, including increased arterial compliance and reduced vascular resistance. Outside of pregnancy, relaxin plays a major role in the protection of organs from excess extracellular matrix accumulation, as demonstrated by the relaxin-null mouse, which develops widespread fibrosis with ageing. Relaxin reduces scarring due to excess collagen deposition by inhibiting collagen production while simultaneously promoting its degradation and can reduce established fibrosis in several animal models of extracellular matrix-associated disease, including liver fibrosis. Treatment with relaxin reduces the myofibroblastic phenotype of activated hepatic stellate cells, the major hepatic collagen-producing cell in fibrosis and cirrhosis. Relaxin also has haemodynamic effects, including vasodilation, and can reduce portal hypertension associated with cirrhosis. In this review, a brief overview of hepatic fibrosis and the role of the hepatic stellate cell will be presented, followed by an introduction to relaxin and its actions. The use of relaxin to treat preclinical models of fibrotic diseases, including liver diseases, will also be discussed. Finally, the completed, current, and ongoing clinical trials of relaxin in human disease will be described, followed by the limitations and future directions for the use of relaxin for disease treatment.